Генотоксичний вплив деяких пестицидів в тестах на Drosophila melanogaster - Білоконь, С.В. (Фактори експериментальної еволюції організмів, 2015)
Aims. We studied the genotoxic effect of acaricides and fungicides in tests of Drosophila melanogaster. Methods. The
object of the study was to analyze the effect of fungicides «Flint Star», «Previkur Energy» and acaricides «Sanmayt»
and «Omayt» on fecundity and longevity of Drosophila. Mutagenic effects of fungicides were determined according to
Muller-5 (Basc) method. Results. Fecundity of C-S line fl ies was signifi cantly less than the control, both by the number
of pupae and the number of adults in case adding drugs. The reduction of life expectancy of fl ies in the experiment, by
adding to the feeding of fl ies drugs «Sanmayt» and «Flint Star» was marked. By using Muller-5 (Basc) method, the
mutagenic effect of fungicides «Previkur Energy» and «Flint Star» was established. Conclusions. The genotoxic activity
of pesticides in the studied drugs on the basis of fertility and life expectancy of fl ies was found. By using Muller-5 (Basc)
method the mutagenic effect of fungicides «Previkur Energy» and «Flint Star» was set.
Keywords: pesticides, mutagenicity, genotoxicity, fecundity, Drosophila melanogaster.